THEORETICAL STUDIES ON THE MAGNETIC, ELECTRICAL, AND OPTICAL PROPERTIES OF LEAD-FREE FERROELECTRIC Ba(Zr\(_{0.2}\)Ti\(_{0.8}\)O\(_3\)) MATERIALS WITH MANGANESE DOPING - Tien Lam Vu; Hoang Thoan Nguyen; Huu Lam Nguyen; Ngoc Trung Nguyen; Quoc Van Duong; Duc Dung Dang (Tạp chí Khoa học Đại học Đà Lạt)
In this study, we conducted a density functional theory investigation of the structural, electronic, magnetic, and optical properties of manganese-doped lead-free ferroelectric Ba(Zr0.2Ti0.8)O3 (BZT) materials. The electronic structure calculations revealed that pristine BZT material behaves as a p-type semiconductor with direct and indirect bandgaps of 3.18 eV and 2.08 eV, respectively. Upon Mn doping, the bandgap values converge to zero, indicating a transition from semiconductor to metal behavior. Additionally, the asymmetrical spin-polarized density of states and significant magnetic moments, determined through Mulliken population analysis, suggest the induction of magnetism in the BZT material due to Mn doping. Magnetic moments of 0.98 µB/f.u., 0.57 µB/f.u., and 0.87 µB/f.u. were observed when Mn substitutes into Ba, Ti, and interstitial sites, respectively. Furthermore, we observed substantial enhancements in dielectric constants and changes in other properties such as refractive index, loss function, and reflectivity upon Mn doping, suggesting alterations in the optoelectronic properties of the materials. Our findings contribute to the understanding of transition metal-doped lead-free ferroelectric BZT materials and provide more information for the development of future smart electronic and optoelectronic devices.